Investigating EFL Syrian undergraduates' vocabulary size - Daaboul, Maisaa Moustafa; Hossein, Vahid Nimehchisalem (Malaysian Association of Modern Languages, 2017)
Vocabulary knowledge is an important aspect of learning English as a second/foreign language (ESL/ EFL). Previous research has given much attention to ESL/EFL learners’ knowledge of vocabulary by measuring their vocabulary size. Yet, in the EFL Syrian context, there is a rarity of research on learners’ vocabulary size. Therefore, the present study attempted to investigate vocabulary knowledge of English among EFL Syrian learners by measuring their vocabulary size based on a vocabulary size test (VST) adopted from Nation (2006). The study was conducted among 100 Syrian university learners joining English in one private university in Syria. The data collected from the participating students in the form of numerical responses to the vocabulary test was analyzed using descriptive statistics. The results revealed that the Syrian university learners’ overall vocabulary size in English was moderate (M=5.30). Moreover, the scores of the learners across the fourteen 1000-word families/lists of the vocabulary test varied from high to moderate. Based on the results, the study suggested that the average EFL Syrian undergraduates need to expand their vocabulary knowledge through training and instruction on vocabulary-raising awareness.